Optimizing Book Delivery Routes Using Genetic Algorithms: Case Study of Erlangga Publisher Yogyakarta Branch - Damba Saputra Rosa; Asep Setiyono; Yohanes Renaldi Rio Santana; Paulus Mudjihartono (Jurnal Buana Informatika, 2024)
Optimizing Book Delivery Routes Using Genetic Algorithms: Case Study of Erlangga Publisher Yogyakarta Branch. This research aims to find the shortest route for book delivery using the Traveling Salesperson Problem (TSP) approach that is solved by a Genetic Algorithm (GA). The distance between the pair of locations will be known by using the longitude and latitude as the coordinates of the location (the place where books must be dropped and the trip continues). This network of the coordinates of locations is then viewed as TSP, which needs GA to solve the shortest path. Running the program for up to 100 iterations, this study resulted in the shortest route, 356 km in a whole route. Among the previous research, this research has its uniqueness, especially when the problem is viewed as a TSP, and when it comes to the crossover mechanism, it is quite rare. Moreover, the case of the Erlangga publisher is the first case that has used the GA.